Adenosine A(2A) receptors and basal ganglia physiology - Schiffmann, S.N. (2007)
Adenosine A(2A) receptors are highly enriched in the basal ganglia system. They are predominantly expressed in enkephalin-expressing GABAergic striatopallidal neurons and therefore are highly relevant to the function of the indirect efferent pathway of the basal ganglia system. In these GABAergic enkephalinergic neurons, the A(2A) receptor tightly interacts structurally and functionally with the dopamine D(2) receptor. Both by forming receptor heteromers and by targeting common intracellular signaling cascades, A(2A) and D(2) receptors exhibit reciprocal antagonistic interactions that are central to the function of the indirect pathway and hence to basal ganglia control of movement, motor learning, motivation and reward. Consequently, this A(2A) / D(2) receptors antagonistic interaction is also central to basal ganglia dysfunction in Parkinson's disease. However, recent evidence demonstrates that, in addition to this postsynaptic site of action, striatal A(2A) receptors are also expressed and have physiological relevance on presynaptic glutamatergic terminals of the cortico-limbic-striatal and thalamo-striatal pathways, where they form heteromeric receptor complexes with adenosine A(1) receptors. Therefore, A(2A) receptors play an important fine-tuning role, boosting the efficiency of glutamatergic information flow in the indirect pathway by exerting control, either pre- and/or post-synaptically, over other key modulators of glutamatergic synapses, including D(2) receptors, group I metabotropic mGlu(5) glutamate receptors and cannabinoid CB(1) receptors, and by triggering the cAMP-protein kinase A signaling cascade.